Evaluation of an Active Citizenship Intervention Based on Youth-Led Participatory Action Research. (December 2020) - Prati, Gabriele; Mazzoni, Davide; Guarino, Antonella; Albanesi, Cinzia; Cicognani, Elvira
Youth-led participatory action research (YPAR) is a theoretical–methodological approach that has been designed to promote positive development (e.g., well-being and health, social–emotional and cognitive development, academic or career advancement) and civic engagement among young people. Although YPAR holds particular promise, there has been little systematic assessment of its effects. Moreover, no study has investigated the role of YPAR in the promotion of active citizenship. We report on an effectiveness evaluation of a YPAR project designed to promote European active citizenship (i.e., identification and attitudes toward a political entity, institutional trust, participation, and political alienation) and social well-being among adolescents. Our sample included 69 Italian high school students (35 in the intervention group; 34 in the control group). We evaluated the impact of YPAR using a pretest–posttest control group design and fitting the generalized estimating equations procedure. The results showed that participants in the intervention group reported increased scores on social well-being, institutional trust, and participation and decreased scores on political alienation compared with the control group. We found no significant effects for identification as European and attitudes toward a political entity. Findings support the benefits of YPAR in terms of social well-being and active citizenship.